PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI MEDIASI (Studi Pada Dinas Koperasi Dan Usaha Mikro Kecil Menengah Provinsi Jawa Tengah) - Bima Eka Sakti, 1352020032; Setyowati, Widhy (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to investigate the effect of Â "Effect of Environmental Work And Motivation To Performance Through Job Satisfaction As Mediation (Study at Department Koperasi dan Usaha Mikro Kecil Menengah Central Java Province)". The staff at the Department Koperasi dan Usaha Mikro Kecil Menengah Central Java province, research was conducted on employees 120 people, using the data collected with the technique of the population (total sampling). Data Analysis technique used is the test of the validity of the matrix component, with alfha cronbach reliabilias test, multiple regression analysis, t test and r2 with adjusted R-square. Work Environment The results showed a positive and significant impact on job satisfaction, motivation and significant positive effect on job satisfaction, working environment and significant positive effect on performance, motivation and significant positive effect on performance. Furthermore, job satisfaction does not mediate work environment on performance but job satisfaction mediates motivation on performance.Keywords: Work Environment, Motivation, Job Satisfaction and Performance